Criminal Liability for Corporate Crime in Indonesia - Sari, Nur Khalifah Agustin (Fakultas Syariah INSURI Ponorogo, 2023)
Criminal liability for corporate crime in Indonesia has become a topic of increasing interest and importance in recent years. The issue is particularly relevant given the rapid growth of the Indonesian economy and the expanding role of corporations in the country's development. The purpose of this abstract is to provide an overview of the current legal framework in Indonesia for holding corporations criminally liable for their actions, as well as to examine some of the challenges and opportunities associated with enforcing corporate criminal liability in practice. The main sources of corporate criminal liability in Indonesia are the Criminal Code and the Law on Limited Liability Companies. Under these laws, corporations can be held criminally liable for a wide range of offenses, including corruption, environmental crimes, and labor violations. However, the legal framework for corporate criminal liability in Indonesia is still relatively new and untested, and there are a number of challenges to effective enforcement, including limited resources and capacity within law enforcement agencies. Despite these challenges, there are also opportunities for improving the enforcement of corporate criminal liability in Indonesia. For example, recent efforts by the government to strengthen anti-corruption measures and improve transparency and accountability in the business sector have the potential to create a more favorable environment for enforcing corporate criminal liability. Additionally, there is growing awareness among both the public and private sectors of the importance of corporate social responsibility and ethical business practices, which could help to promote greater compliance with the law. In conclusion, while there are challenges to enforcing corporate criminal liability in Indonesia, there are also opportunities for improving the legal framework and enhancing enforcement efforts. The successful implementation of corporate criminal liability will require a collaborative effort between the government, law enforcement agencies, and the business sector to ensure that corporations are held accountable for their actions and that the rule of law is upheld.